IoT : technical challenges and solutions - Pal, Arpan; Purushothaman, Balamuralidhar (Artech House, 2017)
Highlighting the systematic problems Internet of Things is encountering on its journey to mass adoption, this practical resource offers professionals solutions to key questions about IoT systems today, including potential network scalability issues, storage, and computing. -- Edited summary from book.
Keywords: Internet of things.; Machine-to-machine communications.; elektronické knihy; electronic books